2023
DOI: 10.3390/pharmaceutics15051375
|View full text |Cite
|
Sign up to set email alerts
|

Solid Lipid Nanoparticles Hydroquinone-Based for the Treatment of Melanoma: Efficacy and Safety Studies

Abstract: Classical melanoma therapy has several side effects that are responsible for a decrease in the final therapeutic efficacy. It is possible that the drug is degraded before reaching the target site and is metabolized by the body itself, resulting in repeated doses being administered throughout the day and a decrease in patient compliance. Drug delivery systems avoid degradation of the active ingredient, improve release kinetics, prevent the drug from being metabolized before reaching the site of action, and impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 32 publications
0
1
0
Order By: Relevance
“…The evaluation of the sensitizing effect of our compounds was made on a THP-1 cell line and performed by h-CLAT. The h-CLAT was completed as previously shown by Trombino et al [24]. The results obtained, treating THP-1 cells with different serial dilutions of pectin and PELAVF1S, are reported in (Table 6) and confirmed that PELAVF1S shows no sensitization effects.…”
Section: In Vitro Analysis Of Pro-sensitizing Potential (H-clat)supporting
confidence: 68%
See 1 more Smart Citation
“…The evaluation of the sensitizing effect of our compounds was made on a THP-1 cell line and performed by h-CLAT. The h-CLAT was completed as previously shown by Trombino et al [24]. The results obtained, treating THP-1 cells with different serial dilutions of pectin and PELAVF1S, are reported in (Table 6) and confirmed that PELAVF1S shows no sensitization effects.…”
Section: In Vitro Analysis Of Pro-sensitizing Potential (H-clat)supporting
confidence: 68%
“…h-CLAT aims to evaluate whether substances or mixtures cause activation of the immune system, resulting in skin sensitization according to the method described by the Organization for Economic Co-operation and Development (OECD) 442E [24] and in the EURL 158 protocol ECVAM (European Union Reference Laboratory for Alternatives to Animal Testing). The test was performed on THP-1 cells, evaluating the modulation of the expression of two costimulatory molecules, CD54 and CD86, using nickel sulfate (NiSO 4 ) as a positive control.…”
Section: Human Cell Line Activation Test (H-clat)mentioning
confidence: 99%
“…The course of the reaction was followed by thin-layer chromatography of a chloroform/hexane eluent mixture (5:5). The resulting product (ester) was purified by filtration and washing in hot methanol to remove the residual dicyclohexylurea (DCU), i.e., the condensation reaction by-product of DCC with amines and alcohols, formed and the remaining solvent residue [52,53].…”
Section: Synthesis Of Thementioning
confidence: 99%